Promoting Sustainable Growth: The Role of Natural Resource Utilization, Green Investment, Digital Finance, Industrial Usage, Energy Efficiency, and Renewable Energy Consumption - Abdullah, Firdaus; Alomair, Abdulrahman; Sibghatullah, Amena; Al Naim, Abdulaziz S. (International Journal of Energy Economics and Policy, 2024)
The current study investigates how sustainable development can be enhanced by the use of natural resources, green investment, digital finance, industrial usage, energy efficiency, and consumption of renewable energy. To the best of the authors’ knowledge, no prior study has analyzed the role of these factors in sustainable economic growth in Belt and Road Initiative countries. Therefore, to fill this literature gap, the present study analyzes the effect of the above mentioned factors on sustainable economic growth in 20 Belt and Road Initiative countries. Taking the data for the period 2010 to 2020, the study employed the Driscoll-Kraay Standard Error model to carry out the empirical estimation. The findings suggest that digital finance and renewable energy consumption are positively, whereas energy intensity, industrial usage and natural resources are negatively associated with sustainable economic growth in BRI countries. Green investment, however, is not found to be significantly associated with sustainable economic growth. On the basis of the findings, the study suggest the selected countries to gain benefits from the opportunities of digital financial inclusion and renewable energy use. Moreover, the results establish the foundation for policymakers to better craft policies to achieve the goals of the Sustainable Development Goals (SDGs).